Mahabbah Dalam Tasawuf Rabi'ah Al-Adawiyah : Apresiasi Atas Rintisan Mistik Sejati dalam Islam - Ach Maimun (Millah: Journal of Religious Studies, 2004)
This paper aims to discuss on Rabi’ah al-'Adawiyah’s mahabbah teaching as the beginning pattern of  Sufism, In the f irst  century of  Islam, the Sufism life or known as the spiritual life was based on fear (khauf) which then expanded become the resignation (tawakkal) to the God. In the second century, the meaning of  mahabbah or called the divine love was raised and changed toward extreme pole. The figure who starting the change of  mahabbah meaning from rational one to the emotional one was Rabi’ah al-‘Adawiyah. Mahabbah in Sufism discourse is the highest degree in Rabi’ah teaching. The value of  pure love in Sufism life granted the big change toward of  next path of  Sufism. All  Sufi referred to the sincerity found in love of Rabi'ah. Rabi’ah made easy the path of  al-Bisthami, al-Hallaj, al-Ghazali, Ibnu Arabi. Even Jalal al-Din al-Rumi put his art works and Sufism experiences in mahabbah as for  Rabi’ah.